Transdifferentiation of Human Dermal Fibroblasts to Smooth Muscle‐Like Cells to Study the Effect of MYH11 and ACTA2 Mutations in Aortic Aneurysms. Issue 4 (27th January 2017) - Yeung, Kak K.; Bogunovic, Natalija; Keekstra, Niels; Beunders, Adriaan A.M.; Pals, Jorrit; van der Kuij, Kim; Overwater, Eline; Wisselink, Willem; Blankensteijn, Jan D.; van Hinsbergh, Victor W.M.; Musters, Rene J.P.; Pals, Gerard; et al.
Abstract : Within two weeks, we succesfully create smooth muscle‐like cells (SMC; right side of image) from skin fibroblasts (left side of image). The transdifferentianted cells express relevant early and late SMc markers on mRNA and protein level. Our method is suitable for the analysis of unclassified variants on mRNA level in genes that are only expressed in SMC and splice errors can be identified. As the SMC are patient specific, we will use them to further elucidate the pathogenesis of aortic aneurysm in patients with various clinical presentations and genetic profiles. ABSTRACT: Mutations in genes encoding proteins of the smooth muscle cell (SMC) contractile apparatus contribute to familial aortic aneurysms. To investigate the pathogenicity of these mutations, SMC are required. We demonstrate a novel method to generate SMC‐like cells from human dermal fibroblasts by transdifferentiation to study the effect of variants in genes encoding proteins of the SMC contractile apparatus ( ACTA2 and MYH11) in patients with aortic aneurysms. Dermal fibroblasts from seven healthy donors and cells from seven patients with MYH11 or ACTA2 variants were transdifferentiated into SMC‐like cells within a 2‐week duration using 5 ng/ml TGFβ1 on a scaffold containing collagen and elastin. The induced SMC were comparable to primary human aortic SMC in mRNA expression of SMC markers which was confirmed on the protein level by immunofluorescence quantification analysis and Western blotting. In patients with MYH11 or ACTA2 variants, the effect of intronic variants on splicing was demonstrated on the mRNA level in the induced SMC, allowing classification into pathogenic or nonpathogenic variants. In conclusion, direct conversion of human dermal fibroblasts into SMC‐like cells is a highly efficient method to investigate the pathogenicity of variants in proteins of the SMC contractile apparatus.